EFFECTS OF PSYCHOEDUCATION TECHNIQUE ON EXAMINATION MISCONDUCT TENDENCIES OF SECONDARY SCHOOL STUDENTS - Ada Anyamene; Chinyelu Nwokolo; Uju Madegbuna (European Scientific Journal, ESJ, 2015)
This study sought to examine the effects of psychoeducation technique on secondary school students’ examination misconduct tendencies in Anambra State. Four research questions were generated to guide the study and four null hypotheses were tested at the 0.05 level of significance. The design of the study was a quasi-experimental, non-equivalent control group design involving an experimental groups and a control group. The sample consisted of 165 senior secondary school (SSS) class II students selected through purposive sampling technique. The students were exposed to the experimental and control treatments for six weeks. The instrument used for the study was the Examination Misconduct Tendencies Scale (EMTS) which was administered as a pre and posttest. Means, standard deviation and analysis of covariance were used to analyze the data. Major findings of the study showed that psychoeducation technique had significant effect on the reduction of students’ examination misconduct tendencies. It was also effective on the reduction of the examination misconduct tendencies of students in various age groups. It was also found out that Psychoeducation technique was effective in positively modifying urban and rural students’ examination misconduct tendencies. Based on these findings, some recommendations were made which include the use of psychoeducation has been shown to be effective in reducing examination misconduct tendencies, it should be encouraged. Practising school guidance and counsellors should learn to use the therapy to assist students to develop positive examinations conduct tendencies.